Conquering walls, making comebacks lived experiences of injured student athletes and their successful returns. - Agudera, Jann Felix P.; Aguilar, Liane Shane A. (Jann Felix P. Agudera and Liane Shane A. Aguilar, 2019)
The lived experience of an athlete during his/her injured state greatly influences their chances of returning to their sport. The prevailing understanding of the lived experiences of student athletes suggests that they may experience the same types of injuries but differ in how they handled the situation and the environmental feedback they received. Using Interpretative Phenomenological Analysis (IPA), this study explored the lived experiences of Filipino student athletes during the time they were injured, making sense of what made them return to the sport. Focused semi-structured interviews were completed with six college students, with four males and two females. Participants emphasized the role of athletic identity and the accompanying benefits of playing sport as their main reason to start playing. Disturbance on one's athletic identity, negative emotional reactions, and various losses on the athletes were the consequences of incurring injuries. Strategies in reclaiming the disrupted athletic identities and looking at the injury in a more positive light were employed when student athletes were in the process of returning to sport. Future researches could focus on a different context where there is large pool of resources and student athletes are well-supported.